DYSTOCIA IN MARATHWADI BUFFALOES DUE TO FOETAL ASCITES ASSOCIATED WITH DEVELOPMENTAL DEFECTS - PATIL, A D; MARKANDEYA, N M; YADAV, G U; THORAT, M G; MOREGAONKAR, S D (The Indian Journal of Animal Reproduction, 2023)
Foetal ascites, as a cause for maternal dystocia has been reported in two Marathwadi buffaloes.
Keywords: Dystocia; Ascites; Buffalo